Question 9.20: Figure 9.24 shows a rotating platform on which is mounted a ......

Figure 9.24 shows a rotating platform on which is mounted a rectangular parallelepiped shaft (with dimensions b, h, and \ell ) spinning about the inclined axis DE. If the mass of the shaft is m, and the angular velocities ω_p and ω_s are constant, calculate the bearing forces at D and E as a function of Φ and ψ. Neglect gravity, since we are interested only in the gyroscopic forces. (The small extensions shown at each end of the parallelepiped are just for clarity; the distance between the bearings at D and E is \ell.)

9.24
Step-by-Step
The 'Blue Check Mark' means that this solution was answered by an expert.
Learn more on how do we answer questions.

The inertial XYZ frame is centered at O on the platform, and it is right handed (\hat{ I } \times \hat{ J }=\hat{ K }). The origin of the right handed comoving body frame xyz is at the shaft’s center of mass G, and it is aligned with the symmetry axes of the parallelepiped. The three Euler angles \phi, \theta, \text { and } \psi are shown in Figure 9.24. Since θ is constant, the nutation rate is zero \left(\omega_n=0\right) \text {. } Thus, Eqn (9.115) reduces to

\begin{aligned}& \omega_x=\omega_p \sin \theta \sin \psi+\omega_n \cos \psi \\& \omega_y=\omega_p \sin \theta \cos \psi-\omega_n \sin \psi \\& \omega_z=\omega_s+\omega_p \cos \theta\end{aligned}                                (9.115)

\omega_x=\omega_p \sin \theta \sin \psi \quad \omega_y=\omega_p \sin \theta \cos \psi \quad \omega_z=\omega_p \cos \theta+\omega_s                          (a)

Since \omega_{p,} \omega_s, \text { and } \theta are constant, it follows (recalling Eqn (9.106)) that

\omega_p=\dot{\phi} \quad \omega_n=\dot{\theta} \quad \omega_s=\dot{\psi}                             (9.106)

\dot{\omega}_x=\omega_p \omega_s \sin \theta \cos \psi \quad \dot{\omega}_y=-\omega_p \omega_s \sin \theta \sin \psi \quad \dot{\omega}_z=0                           (b)

The principal moments of inertia of the parallelepiped are (Figure 9.10(c))

\begin{aligned}& A=\ell_x=\cfrac{1}{12}  m\left(h^2+\ell^2\right) \\& B=\ell_y=\cfrac{1}{12}  m\left(b^2+\ell^2\right) \\& C=\ell_z=\cfrac{1}{12}  m\left(b^2+h^2\right)\end{aligned}                        (c)

Figure 9.25 is a free-body diagram of the shaft. Let us assume that the bearings at D and E are such as to exert just the six body frame components of force shown. Thus, D is a thrust bearing to which the axial torque T_D is appliedfrom, say, a motor of some kind. At E, there is a simple journal bearing.

From Newton’s laws of motion, we have F _{ net }=m a _{ G }. But G is fixed in inertial space, so a_G=0. Thus,

\left(D_x \hat{ i }+D_y \hat{ j }+D_z \hat{ k }\right)+\left(E_x \hat{ i }+E_y \hat{ j }\right)=0

It follows that

E_x=-D_x \quad E_y=-D_y \quad D_z=0                       (d)

Summing moments about G we get

\begin{aligned}M _{G_{\text {net }}} & =\cfrac{\ell}{2}  \hat{ k } \times\left(E_x \hat{ i }+E_y \hat{ j }\right)+\left(-\cfrac{\ell}{2}  \hat{ k }\right) \times\left(D_x \hat{ i }+D_y \hat{ j }\right)+T_D \hat{ k } \\\\& =\left(D_y \cfrac{\ell}{2}-E_y \cfrac{\ell}{2}\right) \hat{ i }+\left(-D_x \cfrac{\ell}{2}+E_x \cfrac{\ell}{2}\right) \hat{ j }+T_D \hat{ k } \\\\& =D_y \ell \hat{ i }-D_x \ell \hat{ j }+T_D \hat{ k }\end{aligned}

where we made use of Eqn (d)_2. Thus,

M_{x_{\text {net }}}=D_y \ell \quad M_{y_{\text {net }}}=-D_x \ell \quad M_{z_{\text {net }}}=T_D                      (e)

We substitute Eqns (a)e(c) and (e) into Euler’s equations (Eqn (9.72)):

\begin{aligned}& M_{x_{\text {net }}}=A \dot{\omega}_x+(C-B) \omega_y \omega_z \\\\& M_{y_{\text {net }}}=B \dot{\omega}_y+(A-C) \omega_x \omega_z \\\\& M_{z_{\text {net }}}=C \dot{\omega}_z+(B-A) \omega_x \omega_y\end{aligned}                                     (f)

After making the substitutions and simplifying, the first Euler equation, Eqn (f)_1, becomes

D_x=\left\{\cfrac{1}{12} \cfrac{m}{\ell}\left[\left(\ell^2-h^2\right) \omega_p \cos \theta-2 h^2 \omega_s\right] \omega_p \sin \theta\right\} \cos \psi                            (g)

Likewise, from Eqn (f)_2 we obtain

D_y=\left\{\cfrac{1}{12} \cfrac{m}{\ell}\left[\left(\ell^2-b^2\right) \omega_p \cos \theta-2 b^2 \omega_S\right] \omega_p \sin \theta\right\} \sin \psi                        (h)

Finally, Eqn (f)_3 yields

T_D=\left[\cfrac{1}{24}  m\left(b^2-h^2\right) \omega_p^2 \sin ^2 \theta\right] \sin 2 \psi                       (i)

This completes the solution, since E_y=-D_y \text { and } E_z=-D_z. Note that the resultant transverse bearing load V at D (and E) is

V=\sqrt{D_x^2+D_y^2}                              (j)

As a numerical example, let

\ell=1  m \quad h=0.1  m \quad b=0.025  m \quad \theta=30^{\circ} \quad m=10  kg

and

\omega_p=100  rpm =10.47  rad / s \quad \omega_{ s }=2000  rpm =209.4  rad / s

For these numbers, the variation of V and T_D \text { with } \psi are as shown in Figure 9.26.

9.10c
9.25
9.26

Related Answered Questions

Question: 9.12

Verified Answer:

Since the comoving frame is rigidly attached to th...
Question: 9.10

Verified Answer:

From Example 9.5, \left[ I _A\right]=\left[...